Heavy-duty anti-scaling epoxy powder coating as well as preparation method and application thereof

By selecting appropriate components in the epoxy powder coating and optimizing the preparation process, the synthetic filler with sustained release function is formed, which solves the problem of difficulty in achieving corrosion and anti-scaling at the same time in the harsh industrial environment in the prior art, and achieves efficient and reliable coating protection effects.

CN119505631AActive Publication Date: 2025-02-25SHANDONG DONGHONG PIPE IND
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411576843.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-25
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

The prior art is difficult to achieve efficient corrosion and anti-scaling at the same time in harsh industrial environments. Traditional anti-corrosion coatings have limited protection capabilities in high temperature, high humidity and high salinity environments, and the existing anti-scaling methods may affect the environment or have poor results.

Method used

A highly anti-corrosion and anti-scattering epoxy powder coating is adopted. By selecting suitable epoxy resin, curing agent, filler, synthetic filler and other components, and by optimizing the preparation process and synergistic action, synthetic filler with sustained release function is formed to inhibit scaling.

Benefits of technology

It realizes reliable protection of equipment and pipelines in complex industrial environments, significantly improves the adhesion and wear resistance of the coating, reduces the scaling rate and porosity, and enhances the resistance to corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505631A_ABST
    Figure CN119505631A_ABST
Patent Text Reader

Abstract

The invention discloses a heavy-duty anti-scaling epoxy powder coating as well as a preparation method and application thereof, and belongs to the technical field of coatings. The epoxy powder coating comprises the following components in parts by weight: 45-60 parts of epoxy resin, 8-15 parts of a curing agent, 5-25 parts of filler, 5-10 parts of synthetic filler, 1-10 parts of pigment, 0.25-5 parts of a defoaming agent, 0.25-5 parts of a flatting agent, 0.25-5 parts of an antioxidant and 0.25-5 parts of a curing accelerator, and the sum of the components is 100%. The coating has the advantages that the porosity is low (at the level of 1-2), the scaling rate is low (0.687-0.728 * 10 <-3 > (mg / cm < 3 > / h), the pull-off adhesive force is high (the pull-off adhesive force is larger than or equal to 50 Mpa and is remarkably higher than the adhesive strength which is larger than or equal to 20 Mpa and specified by the standard SY / T0442-2018), the cathodic disbonding force is small (the cathodic disbonding force is only 2.3-2.5 mm within 48 h at the temperature of 65 DEG C, 1.5 V and is 20-24 mg in the CS-17 round), the wear resistance is good (1 kg / 1000 r, and the wear resistance is 20-24 mg in the CS-17 round), and the coating can pass impact experiments at the temperature of- The coating can adapt to complicated and harsh industrial environments such as petrochemical engineering, ocean engineering, heat delivery, water treatment and the like, and provides a reliable protection solution for equipment and pipelines.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a heavy-duty anti-corrosion and anti-scaling epoxy powder coating and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] In many industrial fields such as petrochemicals, marine engineering, heat transmission, and water treatment, equipment and pipelines are in harsh environments for a long time and face serious corrosion and scaling problems. From the perspective of corrosion, traditional anti-corrosion coatings such as ordinary paint coatings have limited protection capabilities in extreme environments such as high temperature, high humidity, strong acid and alkali, and high salinity. For example, in the marine environment, the high salinity and rich microorganisms of seawater can easily damage ordinary anti-corrosion coatings, causing metal equipment to be corroded; equipment in the petrochemical field is exposed to corrosive chemicals, and traditional anti-corrosion measures are difficult to be effective in the long term. In terms of scaling, in the thermal transmission system, water is heated and evaporated to form carbonate scales such as calcium and magnesium ions that adhere to the inner wall of the pipeline. Traditional anti-scaling methods such as the addition of chemical agents require continuous investment and may affect the environment. Some existing coatings have poor anti-scaling effects, and the accumulation of scale layers will reduce heat transfer efficiency, increase operating costs, and even cause pipeline blockage. Therefore, there is an urgent need for a coating that can simultaneously have high-efficiency heavy-duty anti-corrosion and good anti-scaling functions to meet the protection needs of equipment and pipelines in complex industrial environments. Summary of the invention

[0004] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide a heavy-duty anti-corrosion and anti-scaling epoxy powder coating that can adapt to harsh environments and can effectively resist corrosion and inhibit scaling at the same time. Through research on the selection of coating materials, optimization of preparation processes, and the synergistic effects of various components, it aims to provide a reliable protective coating solution for industrial equipment and pipelines.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] In the first aspect, the present invention provides a heavy-duty anti-corrosion and anti-fouling epoxy powder coating, which comprises the following components in parts by weight: 45-60 parts of epoxy resin, 8-15 parts of curing agent, 5-25 parts of filler, 5-10 parts of synthetic filler, 1-10 parts of pigment, 0.25-5 parts of defoaming agent, 0.25-5 parts of leveling agent, 0.25-5 parts of antioxidant, and 0.25-5 parts of curing accelerator, and the sum of each component is 100%.

[0007] In one or more embodiments, the epoxy resin includes at least one of Dow Chemical DER663U, DER663UE, Jiangsu Sanmu SM601, SM601R, 602R, or SM604.

[0008] In one or more embodiments, the curing agent includes at least one of SI Group T6000 modified alkylphenol formaldehyde resin, Sumitomo Chemical Sumiliteresin PR-50869B, or Kolon PFR.

[0009] In one or more embodiments, the filler includes at least one of Perstorp needle-shaped wood fiber with a mesh size of ≥3000 mesh, Tatsumori needle-shaped wollastonite from Japan, Omya needle-shaped calcium carbonate from Germany, 3M ceramic microspheres W-410, high-gloss barium sulfate YL-909 or NB-806.

[0010] In one or more embodiments, the pigment includes at least one of titanium dioxide, permanent red, permanent violet, phthalocyanine blue, or medium chrome yellow.

[0011] In one or more embodiments, the defoamer includes at least one of BYK-1765, BYK-1690SD, BYK-1691SD, or BYK-1788.

[0012] In one or more embodiments, the leveling agent includes at least one of CLAYTONE-VZ, RHEOBYK-7405, or RHEOBYK-7502.

[0013] In one or more embodiments, the antioxidant includes at least one of the antioxidants RIANOX1010 and BASFIR GANOXB900.

[0014] In one or more embodiments, the curing accelerator includes at least one of Alzchem DYHARD-100S and CUREZOL 2MZ-A.

[0015] In one or more embodiments, the synthetic filler includes an intermediate and a coating material coating the intermediate, wherein the intermediate includes an antiscalant and a nanomaterial, wherein the mass ratio of the antiscalant to the nanomaterial is (0.5-5):(2-10), and the mass ratio of the intermediate to the coating material is (1-2):(0.2-5).

[0016] Furthermore, the scale inhibitor is one or more of polyaspartic acid (PASA) and polyepoxysuccinic acid (PESA). The nanomaterial is one or more of nano-SiO2 and coal-based columnar nano-activated carbon. The coating material is polyethylene glycol-polylactic acid (PEG-PLA) or polyethylene glycol-polycaprolactone (PEG-PCL).

[0017] In a second aspect, the present invention provides a method for preparing the above-mentioned heavy-duty anti-corrosion and anti-fouling epoxy powder coating, comprising the following steps:

[0018] The epoxy resin, curing agent, filler, synthetic filler, pigment, defoamer, leveling agent, antioxidant and curing accelerator are mixed and dispersed, extruded, crushed and screened to obtain epoxy powder;

[0019] The epoxy powder is coated on the surface of the object to be coated, and dried to obtain the heavy-duty anti-corrosion and anti-scaling epoxy powder coating.

[0020] In one or more embodiments, the method for preparing the synthetic filler comprises the following steps: mixing the nanomaterial and the antiscalant solution, heating and evaporating to prepare an intermediate; mixing the intermediate and the coating material solution, heating and evaporating to prepare the synthetic filler.

[0021] Furthermore, the antiscalant solution is a 40-60 wt. % antiscalant aqueous solution, preferably 50 wt. %.

[0022] Furthermore, after the nanomaterial and the antiscalant solution are mixed, ultrasonic dispersion is performed on them for 5-60 minutes, preferably 5-10 minutes.

[0023] Furthermore, when the intermediate is prepared by heating and evaporation, the heating temperature is 50-80° C., the relative pressure is -0.2 to -0.1 MPa, and the evaporation time is 1-12 h, preferably 1-3 h.

[0024] Furthermore, the coating material solution is a dichloromethane solution of the coating material with a mass fraction of 5-15 wt.%, preferably 10 wt.%.

[0025] Furthermore, after the intermediate and the coating material solution are mixed, they are subjected to ultrasonic dispersion for 5-10 minutes.

[0026] Furthermore, when the synthetic filler is prepared by heating and evaporation, the heating temperature is 40-60°C, the relative pressure is -0.2 to -0.1 MPa, and the evaporation time is 1-6 hours.

[0027] In one or more embodiments, the mixing and dispersing is uniformly dispersing in a high-speed mixer, wherein the rotation speed is 800-1000 r / min and the mixing time is 30-45 minutes.

[0028] In one or more embodiments, the extrusion is performed by a twin-screw extruder, wherein the rotation speed is set to 15-20 r / min, the temperature of the first zone is set to 70-75° C., and the temperature of the second zone is set to 100-110° C.

[0029] In one or more embodiments, the crushing is performed by crushing with a crusher after extrusion, wherein the crushing speed is 500-600 r / min and the crushing time is 10-15 minutes.

[0030] In one or more embodiments, the screening is to sieve out 120-150 mesh powder of the crushed material through a vibrating screen for use, preferably 140 mesh.

[0031] In one or more embodiments, before the epoxy powder is coated on the surface of the object to be coated, the object to be coated is subjected to a heating treatment at a temperature of 160-170°C.

[0032] In one or more embodiments, the epoxy powder is coated on the surface of the object to be coated by spraying, the spraying interval is 1-2 seconds, and the spraying is continuous at intervals to achieve a thickness of 300-400 μm.

[0033] In one or more embodiments, the drying is performed at 160-170° C. for 15-20 minutes.

[0034] In a third aspect, the present invention provides a pipeline comprising the above-mentioned heavy-duty anti-corrosion and anti-scaling epoxy powder coating.

[0035] In a fourth aspect, the present invention provides a device comprising the above-mentioned heavy-duty anti-corrosion and anti-fouling epoxy powder coating.

[0036] The beneficial effects of the present invention are:

[0037] (1) The present invention provides a heavy-duty anti-corrosion and anti-fouling epoxy powder coating, comprising a synthetic filler with a slow-release function. Due to the unique preparation method of the synthetic filler with a slow-release function, the scaling rate range is 0.687-0.728×10-3 (mg / cm 3 / h), showing unique advantages in scale inhibition. Without affecting the performance of the coating, the generation of precipitation crystals is effectively reduced, thereby controlling the scaling rate at a low level. Compared with traditional coatings, the coating of the present invention can more effectively prevent the adverse effects of scaling on coating performance.

[0038] (2) The present invention provides a unique synthetic filler with a slow-release function, which uses a specific scale inhibitor and a nanomaterial to form an intermediate, which can slowly release the scale inhibitor component on the coating surface under the condition of contact with water. At the same time, the intermediate is coated with a coating material, which can significantly reduce the adverse reaction between the scale inhibitor and the coating.

[0039] (3) The present invention provides a heavy-duty anti-corrosion and anti-scaling epoxy powder coating, whose pull-off adhesion (MPa) / bonding strength is ≥50Mpa, and the cathode stripping (65°C, 1.5V, 48h) is only 2.3-2.5mm. The adhesion of the coating is significantly higher than the bonding strength ≥20Mpa specified in the standard SY / T0442-2018, which is mainly attributed to the reasonable proportion of each component in the present invention, especially the dense polymer network structure synergistically constructed by the epoxy resin and the curing agent phenolic resin, and the cross-linking density improved by the imidazole and dicyandiamide curing accelerators. This unique structure formed by scientific and reasonable proportioning makes the internal pores of the coating extremely small and the stability is extremely high, which can effectively block the penetration of corrosive media. Compared with traditional coatings, the porosity is greatly reduced, thereby achieving a qualitative improvement in adhesion, thereby significantly reducing the risk of corrosion caused by cathode stripping.

[0040] (4) The wear resistance (1kg / 1000r, CS-17 wheel) of the coating of the present invention is 20-24mg, and it has passed the -30℃, 5J impact test. This excellent performance is mainly attributed to the reasonable selection and precise use of fillers. In the use of fillers, needle-shaped, flaky, and spherical fillers were selected, and these fillers were evenly and stably dispersed in the entire coating system by controlling the ratio. These fillers are equivalent to numerous tiny reinforcing units in the coating. When the coating is subjected to external forces (such as friction, scratches, impact resistance, etc.), the fillers can effectively disperse and bear the external stress by virtue of their own structural characteristics, thereby significantly reducing the stress concentration borne by the coating body and avoiding defects such as cracks and breakages in the coating prematurely.

[0041] (5) The porosity of the coating of the present invention is at the level of 1 to 2. This is because the proportions of the various components in the formula are reasonable, and the imidazole or dicyandiamide curing accelerators fully play their role, greatly improving the crosslinking density of the coating, making the internal molecular structure of the coating more compact, and effectively reducing the formation of pores.

[0042] (6) The coating of the present invention has low porosity (at level 1 to 2), low scaling rate (0.687-0.728×10-3 (mg / cm 3 / h)), high adhesion by pull-off method (≥50Mpa, significantly higher than the bonding strength ≥20Mpa specified in standard SY / T0442-2018), small cathodic peeling (65℃, 1.5V, 48h is only 2.3-2.5mm), good wear resistance (1kg / 1000r, CS-17 wheel is 20-24mg), and can pass the -30℃, 5J impact test and other advantages. The coating can adapt to complex and harsh industrial environments such as petrochemical, marine engineering, thermal transmission, water treatment, etc., and provide reliable protection solutions for equipment and pipelines. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0044] Figure 1 This is a scanning electron microscope image of Example 1 of the present invention after the scaling rate test; wherein a is a distorted CaCO3 crystal, and b is the morphology of the synthetic filler on the coating surface;

[0045] Figure 2 This is a scanning electron microscope image of comparative example 3 of the present invention after the scaling rate test, a is a conventional CaCO3 crystal;

[0046] Figure 3 The porosity of the bonding surface of Example 1 of the present invention was observed under a 40x magnifying glass;

[0047] Figure 4 The porosity of the bonding surface of Comparative Example 1 of the present invention was observed under a 40x magnifying glass. DETAILED DESCRIPTION

[0048] All reagents are commercially available.

[0049] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0050] Example 1

[0051] S1. Synthetic filler:

[0052] 10 parts of nano-SiO2 were weighed and mixed with 1 part of 50wt.% polyepoxysuccinic acid (PESA) aqueous solution, and ultrasonically dispersed for 10 minutes; then transferred to a round-bottom flask, and continuously evaporated for 3 hours using a rotary evaporator at 70°C and a relative pressure of -0.2MPa until the solvent was completely volatilized, thereby obtaining a SiO2 / PASP intermediate. Then, 1 part of the SiO2 / PASP intermediate was mixed with 2 parts of 10wt.% polyethylene glycol-polylactic acid (PEG-PLA) dichloromethane solution, and ultrasonically dispersed for 10 minutes, and then transferred to a round-bottom flask, and continuously evaporated for 4 hours using a rotary evaporator at 60°C and a relative pressure of -0.2MPa until the solvent was completely volatilized, thereby obtaining a synthetic filler.

[0053] S2, heavy-duty anti-corrosion and anti-scaling functional coating components include:

[0054] The epoxy resins used were Dow Chemical DER663U (30 parts) and DER663UE (29.5 parts);

[0055] The curing agent is Sumiliteresin PR-50869B, and the dosage is (15 parts);

[0056] The fillers used were Perstorp needle-shaped wood fiber (3 parts), 3M ceramic microspheres W-410 (4 parts), and high-gloss barium sulfate YL-909 (8 parts);

[0057] Synthetic filler (5 parts);

[0058] The pigments are phthalocyanine blue (0.5 parts) and titanium dioxide (1 part);

[0059] The defoamer is BYK-1691SD (1 part);

[0060] Leveling agent RHEOBYK-7405 (1.5 parts);

[0061] Antioxidant BASFIR GANOX B900 (1 part);

[0062] The curing accelerator was Alzchem DYHARD-100S (0.5 parts).

[0063] S3. The preparation method of the heavy-duty anti-corrosion and anti-scaling functional coating is as follows:

[0064] The components of S2 were evenly dispersed in a high-speed mixer (speed of 1000 r / min, mixing time of 30 minutes), and then extruded using a double-roll extruder (speed set to 20 r / min), with the temperature of zone one set to 75°C and the temperature of zone two set to 100°C; after extrusion, they were crushed using a pulverizer (crushing speed of 600 r / min, crushing time of 15 minutes), and then 140-mesh powder was sieved out through a vibrating screen; the experimental steel parts (no restrictions on model and size) were heated to 160°C in an oven, and then the 140-mesh powder was sprayed onto the steel parts using an intelligent spray gun system to make the coating thickness reach 300-400um, and then placed in an oven and baked at 160°C for 20 minutes, and finally the samples were taken out and allowed to cool naturally.

[0065] Example 2

[0066] The difference from Example 1 is that step S1 is different. Specifically, it is:

[0067] S1: Weigh 10 parts of nano-coal columnar nano-activated carbon and 1 part of 50wt% polyepoxysuccinic acid (PESA) aqueous solution, and ultrasonically disperse it for 10 minutes; then transfer it to a round-bottom flask, and use a rotary evaporator to evaporate continuously for 3 hours at 70°C and a relative pressure of -0.2MPa until the solvent is completely volatilized, thereby obtaining a C / PASP intermediate. Then take 1 part of SiO2 / PASP intermediate and mix it with 2 parts of 10wt% polyethylene glycol-polylactic acid (PEG-PLA) dichloromethane solution, and then ultrasonically disperse it for 10 minutes, and then transfer it to a round-bottom flask, and use a rotary evaporator to evaporate continuously for 4 hours at 60°C and a relative pressure of -0.2MPa until the solvent is completely volatilized, thereby obtaining a synthetic filler.

[0068] Comparative Example 1

[0069] The difference from Example 1 is that step S1 is different. Specifically, it is:

[0070] S1: Weigh 10 parts of nano-coal columnar nano-activated carbon and 1 part of a 50wt% polyepoxysuccinic acid (PESA) aqueous solution, mix them, and ultrasonically disperse them for 10 minutes; then transfer them to a round-bottom flask and use a rotary evaporator to evaporate continuously for 3 hours at 70°C and a relative pressure of -0.2MPa until the solvent is completely evaporated, thereby obtaining a SiO2 / PASP intermediate.

[0071] Comparative Example 2

[0072] The difference from Example 1 is that step S1 is different. Specifically, it is:

[0073] S1: Weigh 10 parts of nano-coal columnar nano-activated carbon and 2 parts of 10wt% polyethylene glycol-polylactic acid (PEG-PLA) dichloromethane solution, then ultrasonically disperse for 10 minutes, then transfer to a round-bottom flask, and use a rotary evaporator to continuously evaporate for 3 hours at 60°C and a relative pressure of -0.2MPa until the solvent is completely volatilized, thereby obtaining a synthetic filler.

[0074] Comparative Example 3

[0075] The difference from Example 1 is that step S1 is omitted and no synthetic filler is prepared; the synthetic filler in step S2 is 0 parts, and the other components are the same as those in step S2 of Example 1; and the conditions of step S3 are the same as those of step S3 of Example 1.

[0076] Performance Test:

[0077] 1. Anti-corrosion test:

[0078] The coatings prepared in Examples 1-2 and Comparative Examples 1-3 were subjected to relevant anti-corrosion tests according to the reference standard. The test results are shown in Table 1 below.

[0079] Table 1

[0080]

[0081] 2. Anti-scaling test:

[0082] Scaling rate test: Examples 1-2 and Comparative Examples 1-3 were made into 50*100*1mm sample plates, and then placed in 0.01mol / L CaCl2, 0.01mol / L NaHCO3 aqueous solution, and immersed for 24 hours at 70°C and 1000r / min for testing. The scaling test results are shown in Table 2 below.

[0083] Table 2

[0084]

[0085] It can be seen from Table 1 and Table 2 that only the coatings prepared in Examples 1 and 2 can simultaneously have the functions of heavy-duty corrosion protection and anti-scaling. The scaling rate is (0.625-0.750)×10 -3 (mg / cm 3 / h), preferably (0.687-0.728)×10 -3 (mg / cm 3 / h).

[0086] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A heavy-duty anti-corrosion and anti-fouling epoxy powder coating, characterized in that: According to weight components, the invention comprises the following components: 45-60 parts of epoxy resin, 8-15 parts of curing agent, 5-25 parts of filler, 5-10 parts of synthetic filler, 1-10 parts of pigment, 0.25-5 parts of defoaming agent, 0.25-5 parts of leveling agent, 0.25-5 parts of antioxidant and 0.25-5 parts of curing accelerator, and the sum of all components is 100%.

2. The heavy duty anti-corrosion and anti-fouling epoxy powder coating according to claim 1, characterized in that: The epoxy resin includes at least one of Dow Chemical DER663U, DER663UE, Jiangsu Sanmu SM601, SM601R, 602R or SM604; Preferably, the curing agent includes at least one of the following: US SI Group T6000 modified alkylphenol formaldehyde resin, Japan Sumitomo Chemical Sumiliteresin PR-50869B or South Korea Kolon PFR; Preferably, the filler includes at least one of Perstorp needle-shaped wood fiber with a mesh size of ≥3000 from Finland's Perstorp, Tatsumori needle-shaped wollastonite from Japan's Longsen, Omya needle-shaped calcium carbonate from Germany, 3M ceramic microspheres W-410, high-gloss barium sulfate YL-909 or NB-806; Preferably, the pigment includes at least one of titanium dioxide, permanent red, permanent violet, phthalocyanine blue or medium chrome yellow; Preferably, the defoamer comprises at least one of BYK-1765, BYK-1690SD, BYK-1691SD or BYK-1788; Preferably, the leveling agent includes at least one of CLAYTONE-VZ, RHEOBYK-7405 or RHEOBYK-7502; Preferably, the antioxidant includes at least one of the antioxidants RIANOX1010 and BASFIR GANOXB900; Preferably, the curing accelerator includes at least one of Alzchem DYHARD-100S and CUREZOL 2MZ-A.

3. The heavy-duty anti-corrosion and anti-fouling epoxy powder coating according to claim 1, characterized in that: The synthetic filler includes an intermediate and a coating material coating the intermediate, wherein the intermediate includes an antiscalant and a nanomaterial; Preferably, the mass ratio of the scale inhibitor to the nanomaterial is (0.5-5):(2-10), and the mass ratio of the intermediate to the coating material is (1-2):(0.2-5); Preferably, the scale inhibitor is one or more of polyaspartic acid or polyepoxysuccinic acid; Preferably, the nanomaterial is one or more of nano-SiO2 and coal-based columnar nano-activated carbon; Preferably, the coating material is polyethylene glycol-polylactic acid or polyethylene glycol-polycaprolactone.

4. The method for preparing the heavy-duty anti-corrosion and anti-fouling epoxy powder coating according to any one of claims 1 to 3, characterized in that: The steps include: The epoxy resin, curing agent, filler, synthetic filler, pigment, defoamer, leveling agent, antioxidant and curing accelerator are mixed and dispersed, extruded, crushed and screened to obtain epoxy powder; The epoxy powder is coated on the surface of the object to be coated, and dried to obtain the heavy-duty anti-corrosion and anti-scaling epoxy powder coating.

5. The method for preparing the heavy-duty anti-corrosion and anti-fouling epoxy powder coating according to claim 4, characterized in that: The preparation method of the synthetic filler comprises the following steps: mixing the nano material and the antiscalant solution, heating and evaporating to prepare the intermediate; mixing the intermediate and the coating material solution, heating and evaporating to prepare the synthetic filler.

6. The method for preparing the heavy-duty anti-corrosion and anti-fouling epoxy powder coating according to claim 5, characterized in that: The antiscalant solution is a 40-60wt.% antiscalant aqueous solution; After the nanomaterial and the antiscalant solution are mixed, ultrasonic dispersion is performed for 5-60 minutes; When the intermediate is prepared by heating and evaporation, the heating temperature is 50-80°C, the relative pressure is -0.2 to -0.1 MPa, and the evaporation time is 1-12 hours; The coating material solution is a dichloromethane solution of the coating material with a mass fraction of 5-15wt.%; After the intermediate and the coating material solution are mixed, ultrasonic dispersion is performed for 5-10 minutes; When the synthetic filler is prepared by heating and evaporation, the heating temperature is 40-60°C, the relative pressure is -0.2 to -0.1 MPa, and the evaporation time is 1 to 6 hours.

7. The method for preparing the heavy-duty anti-corrosion and anti-fouling epoxy powder coating according to claim 4, characterized in that: The mixing and dispersion is uniformly dispersed in a high-speed mixer, wherein the rotation speed is 800-1000r / min and the mixing time is 30-45 minutes; Preferably, the extrusion is performed by a twin-screw extruder, wherein the speed is set to 15-20 r / min, the temperature of the first zone is set to 70-75° C., and the temperature of the second zone is set to 100-110° C.; Preferably, the crushing is performed by crushing with a crusher after extrusion, wherein the crushing speed is 500-600r / min and the crushing time is 10-15 minutes; Preferably, the screening is to sieve the crushed material through a vibrating screen to obtain 120-150 mesh powder for later use.

8. The method for preparing the heavy-duty anti-corrosion and anti-fouling epoxy powder coating according to claim 4, characterized in that: Before the epoxy powder is coated on the surface of the object to be coated, the object to be coated is subjected to a heating treatment, and the heating time is 160-170°C; Preferably, the epoxy powder is coated on the surface of the object to be coated by spraying, the spraying interval is 1-2 seconds, and the spraying is continuous at intervals to make the thickness reach 300-400 μm; Preferably, the drying is carried out at 160-170° C. for 15-20 minutes.

9. A pipeline, characterized in that: The invention comprises the heavy-duty anti-corrosion and anti-fouling epoxy powder coating according to any one of claims 1 to 3 or the heavy-duty anti-corrosion and anti-fouling epoxy powder coating prepared by the preparation method according to any one of claims 4 to 8.

10. A device, characterized in that: The invention comprises the heavy-duty anti-corrosion and anti-fouling epoxy powder coating according to any one of claims 1 to 3 or the heavy-duty anti-corrosion and anti-fouling epoxy powder coating prepared by the preparation method according to any one of claims 4 to 8.

Citation Information

Patent Citations

  • Novel anti-scaling coating

    CN106497326A

  • Scale inhibition particle and preparation method and application thereof

    CN112080264A

  • Special heavy-duty anti-corrosion sintered epoxy powder coating for roller coating of large-diameter steel pipe and preparation method of special heavy-duty anti-corrosion sintered epoxy powder coating

    CN113930133A

  • Weather-resistant self-repairing coating and preparation method thereof

    CN114196309A

  • Solid slow-release scale inhibition material and preparation method thereof

    CN114560571A